Formação continuada de professores como um projeto coletivo e de identidade profissional - Costa, Kelle Cristina da Silva Vital [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
This research is part of the field of teacher training, especially developed the topic of continuing education. There is, according to the literature, the importance of this training for teachers as a sort of continuum, trajectory in which the teacher will (re) building their knowledge throughout their lives, in order to provide knowledge and values that add to your practice teaching. However, often the training activities are designed for knowledge transmitter model forming agent for the teacher, disregarding the different contexts of school communities, this strategy which hardly reaches the real needs of teachers in their daily lives. It is evident, too, the need to provide, in training moments, spaces to engage in dialogue and reflect on the teachers profession today, (re) building thus their teacher identity. In this context, the objective of this research is to examine whether the continued formation is configured as a collective construction and as a space for reflection on what it means to be a teacher. The research is characterized by a qualitative approach, and to collect data, we used the semi-structured interview technique. Participants were five teachers in the areas of Physical Education, History, English, Portuguese and Mathematics, a state school Treble city education (SP). The results show the importance of continuing education for teachers, which provides reflections, discussions, acquisition of knowledge and skills that contribute to its performance, motivating and developing strategies to enable them to face the challenges of everyday life and reflect collectively on what it means to be a teacher. It was concluded that continuing education for this group of teachers is configured as a space for collective construction, which together with other teachers rethink, reflect and continuously reconstruct their practices and objectives, and enables reflection on the teaching profession constantly. It will be essential, therefore...

A presente pesquisa insere-se no campo da formação de professores, especialmente tematizando a formação continuada. Verifica-se, conforme a literatura, a importância desta formação para os docentes como uma espécie de continnum, trajetória na qual o professor vai (re)construindo seu conhecimento por toda a vida, de modo a proporcionar saberes e valores que agreguem na sua prática pedagógica. Porém, frequentemente as ações formativas são concebidas pelo modelo transmissor de conhecimentos do agente formador para o professor, desconsiderando os diferentes contextos das comunidades escolares, estratégia esta que dificilmente alcança as reais necessidades dos professores em seu cotidiano. Evidencia-se, também, a necessidade de proporcionar, nos momentos de formação, espaços para os professores dialogarem e refletirem sobre a profissão na atualidade, (re)construindo desse modo a sua identidade docente. Diante desse contexto, o objetivo desta pesquisa consiste em analisar se a formação continuada se configura como uma construção coletiva e como um espaço para a reflexão sobre o que significa ser professor. A pesquisa caracteriza-se pela abordagem qualitativa, e, para a coleta de dados, foi utilizada a técnica de entrevista semiestruturada. Os participantes foram cinco professores das áreas de Educação Física, História, Inglês, Língua Portuguesa e Matemática, de uma escola da rede estadual de ensino da cidade de Agudos (SP). Os resultados evidenciam a importância da formação continuada para os docentes, a qual proporciona reflexões, discussões, aquisição de saberes e conhecimentos que contribuem para sua atuação, motivando-os e desenvolvendo estratégias para que possam enfrentar os desafios do dia a dia e refletir coletivamente sobre o que significa ser professor. Conclui-se que a formação continuada para este grupo de professores se configura como espaço para construção coletiva, no qual juntamente com..
Keywords: Professores - Formação; Educação permanente; Identidade profissional; Profissões de nivel superior; Teachers, Training of